Composition for producing pearl wool, novel quick-dry soft high-resilience material as well as preparation method and application of novel quick-dry soft high-resilience material

The composition of high-pressure low-density polyethylene, micron silica aerogel and nano silica, combined with talc powder and anti-shrinkage agent, is prepared to prepare a quick-drying, soft and highly rebound pearl cotton material, solving the existing solution The problem of pearl cotton material being easy to collapse and difficult to dry has improved the comprehensive performance and service life of the material, and adapted to modern life needs.

CN119176980APending Publication Date: 2024-12-24QINGDAO VANKING LIVING CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411464308.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2024-12-24

AI Technical Summary

Technical Problem

The existing pearl cotton filling materials are prone to collapse and have poor durability during use, and are difficult to dry after washing, which is prone to breed bacteria, affecting health and odor, and difficult to adapt to the requirements of modern fast-paced life.

Method used

Using high-pressure low-density polyethylene, micron silica aerogel and nano silica composition, a quick-drying, soft and highly rebound pearl cotton material is prepared by extrusion molding, combining talc powder and anti-shrinkage agent. , optimize the molding temperature and process parameters to improve the overall performance of the material.

Benefits of technology

It has achieved the rapid drying, compression elasticity and softness of pearl cotton materials, and is suitable for filling materials for home textile and home products, improving service life and hygiene, and adapting to modern living needs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005092970570000091
    Figure BDA0005092970570000091
  • Figure BDA0005092970570000101
    Figure BDA0005092970570000101
Patent Text Reader

Abstract

The invention relates to a composition for producing pearl wool, a novel quick-dry soft high-resilience material, a preparation method and application, and the technical scheme is that the composition for producing the pearl wool comprises the following components in parts by weight: 100 parts of high-pressure low-density polyethylene; more than 0 and 2 parts of micron silicon dioxide aerogel; and more than 0 and 2 parts of nano silicon dioxide. The pearl wool product prepared from the composition has the characteristics of quick drying, softness and high resilience, can be used as a filling material of home textile and household products such as quilts, mattresses, seat cushions, pillows, neck pillows, carpets, quilting cushions, Simmons mats and sofas, and can also be directly used as cushions of various articles.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a composition for producing pearl cotton, a novel quick-drying soft high-rebound material, a preparation method and an application thereof. Background Art

[0002] Highly foamed polyethylene (EPE) is a product made by extrusion or injection molding with LDPE as the main raw material, adding foaming agent and other processing aids. It is a kind of polymer material formed by a large number of gas micropores dispersed in solid plastic (polyethylene). It has the characteristics of high strength, light weight, sound absorption, shock absorption, and cushioning. It is widely used in the outer packaging of furniture, household appliances, instruments and meters, craft gifts, etc.; building waterproof and sound insulation materials; floor moisture-proof and heat-insulating mats; various sports goods and other fields. It has a non-cross-linked closed-cell structure, soft texture, elasticity, water-proof and moisture-proof, quick-drying, shock-proof and impact-resistant properties, can be recycled and reused repeatedly, is non-toxic, and is a widely used environmentally friendly material.

[0003] Document CN107057166A discloses an odorless PE foam material and a manufacturing method thereof. The odorless PE foam material is mainly manufactured from the following raw materials in parts by weight: 50-100 parts of LDPE, 10-40 parts of filler, 1-10 parts of modified foaming agent, 0.1-5 parts of auxiliary foaming agent, 0.1-10 parts of lubricant, and 0.5-1 part of odorless cross-linking agent. Document N116731379A discloses a method for preparing an environmentally friendly EPE pearl cotton material, which relates to the technical field of EPE pearl cotton, and specifically to a method for preparing an environmentally friendly EPE pearl cotton material, comprising the following steps: S1, putting 7 parts of titanium dioxide and 8 parts of calcium carbonate into a ball mill, adding an appropriate amount of anhydrous ethanol for wet ball milling, and the rotation speed of the ball mill is 1200-1500 rpm. The preparation method of the flame-retardant pearl cotton material of the present invention adopts wet ball milling of titanium dioxide, calcium carbonate and anhydrous ethanol, and then ultrasonically disperses the ball mill mixed slurry with asbestos fiber and vinyl bisstearamide to obtain a preliminary mixture, and at the same time, low-density polyethylene, isobutyl triethoxysilane and sodium lignin sulfonate are mixed once, and then polychloroprene, sodium alginate and an active agent are added for secondary mixing to obtain a secondary mixture, and finally the aforementioned preliminary mixture and the secondary mixture are reacted with an antistatic agent and a foaming agent under high pressure and high temperature, and the finished material is obtained after extrusion molding and cooling.

[0004] Document JP2019127143 provides a foam that can take into account both temperature sensitivity and cushioning (cushioning). The content of zirconium oxide is 0.01 to 8 parts by mass relative to 100 parts by mass of the resin component. In the foam, the zirconium oxide is dispersed in the resin component as a dispersed phase with an average diameter of less than 10 μm. The foaming ratio of the foam can be 10 or more. The thermoplastic resin can have an olefin resin. The resin component can be a polyethylene resin. The foam can also have silicon oxide. Zirconium oxide can be positioned on the wall surface of the cavity and / or near the surface layer. The foam can be a temperature-sensitive foam that can release heat.

[0005] Document EP22883264 discloses a polyethylene-based resin foamed bead and a method for preparing the same, wherein the polyethylene-based resin foamed bead comprises a mixed resin of virgin polyethylene (A) and recycled polyethylene (B) as a base resin. The mixed resin comprises a predetermined proportion of virgin polyethylene (A) and recycled polyethylene (B). The virgin polyethylene (A) is a linear low-density polyethylene (A1) having specified physical properties obtained by polymerization using a metallocene-based polymerization catalyst. Recycled polyethylene (B) is a post-consumer material containing linear low-density polyethylene (B1) and low-density polyethylene (B2) and having linear low-density polyethylene (B1) as the main component.

[0006] EP22883263 discloses a method for producing polyethylene-based resin expanded beads, which make it possible to produce expanded bead molded products with high flexibility and excellent surface smoothness under excellent molding conditions. In addition, an inorganic physical foaming agent can be used as a foaming agent to produce the expanded beads. This makes it possible to avoid the use of organic physical foaming agents and reduce environmental load.

[0007] In Patent Document 1 of Japanese Unexamined Patent Publication No. 2019-38198, a foamed resin laminate is disclosed, which has a phenolic resin foam layer and a surface layer provided on at least one surface of the foam layer by a flexible surface material, wherein the surface layer is a metal layer covered with a protective layer. The document records that the phenolic resin foam layer is used as a heat insulating material in various fields, and in the embodiment, it is recorded that the phenolic resin foam layer is provided on a sloping roof to improve the operability.

[0008] Japanese Patent Application Laid-Open No. 2017-141342 discloses a foam having a skin region and a core region including a thermoplastic resin and an elastomer. In this document, many inorganic compounds are given as examples of fillers that can be included in the foamed molded body, but the particle size is not described, and there is no blending in the examples.

[0009] In Patent Document 3 of Japanese Patent Publication No. 2019-38997, a foamed resin sheet with an adhesive layer is disclosed as a resin sheet for heat dissipation of electronic devices. The document records a thermally conductive adhesive containing first thermally conductive particles with an average particle size of 0.1 μm or more and less than 5 μm and second thermally conductive particles with an average particle size of 5 to 30 μm as an adhesive layer, and the adhesive layer can also be foam. In the embodiment, as an adhesive layer, a non-foamed adhesive layer containing aluminum hydroxide powder with an average particle size of 1 μm and aluminum hydroxide powder with an average particle size of 8 μm was prepared.

[0010] Patent document 4 of utility model registration No. 3113678 discloses a blood flow enhancing sheet having a cross-linked foam structure with at least a sheet-like surface and in which aluminum oxide, titanium oxide, or zirconium oxide is mixed alone or in combination with polyethylene resin.

[0011] In patent document 5 of patent publication No. 2003-327733, the first step of burning inorganic natural mineral colloidal rock to burn colloidal rock and the second step of mixing the above-mentioned burned colloidal rock with 10 to 20 parts of polyethylene resin in a ratio of about 5 parts of metal oxide to 100 parts, and on this basis adding at least a foaming agent to mix and foam to obtain polyethylene foam and the above-mentioned steps.

[0012] The filling materials of home textile and home furnishing products such as quilts, mattresses, sitting cushions, pillows, neck pillows, carpets, quilted pads, Simmons pads, sofas, etc. are required to be fluffy, soft, warm, washable, quick-drying, and have good resilience after repeated use and no compaction. The current market uses polyester fiber mid-cotton filling. The polyester fibers are loosened, combed, and messed up through combing equipment, and then laid into a net. Then, the fibers are fixed into flakes through hot melting or spraying. They are soft and fluffy, but have poor durability and resilience. Mattresses and pads, in particular, are prone to collapse after long use. After washing, due to the large number of gaps between the fibers, a large amount of moisture is easily retained, which is not easy to dry. In rainy weather, it is even more difficult to dry, which leads to the breeding of a large number of bacteria, which not only affects health, but also produces unpleasant odors, making it difficult to adapt to the fast-paced life requirements of modern society. Summary of the invention

[0013] One of the purposes of the present invention is to provide a new composition for producing pearl cotton. The pearl cotton product prepared by the composition has the characteristics of quick drying, softness and high resilience.

[0014] To achieve one of the above purposes, the technical solution of the present invention is:

[0015] The composition for producing pearl cotton comprises, by weight:

[0016] High pressure low density polyethylene, 100 parts;

[0017] Micronized silica aerogel, greater than 0 and 2 parts;

[0018] Nano-silicon dioxide, greater than 0 and 2 parts.

[0019] High-pressure low-density polyethylene, referred to as LDPE.

[0020] In the above technical solution, the preferred LDPE crystallinity is 55% to 60%, for example but not limited to LDPE crystallinity of 56%, 57%, 58%, 59% and the like.

[0021] In the above technical solution, the MFR (i.e., melt flow rate) of LDPE is preferably 1.5-4.5 g / 10 min, for example but not limited to, the MFR of LDPE is 2 g / 10 min, 2.5 g / 10 min, 3 g / 10 min, 3.5 g / 10 min, 4 g / 10 min, etc.

[0022] In the above technical solution, the density of LDPE is preferably 0.9-1.0 g / cm 3 , for example but not limited to LDPE, the density is 0.91 g / cm 3 , 0.92g / cm 3 、0.93g / cm 3 、0.94g / cm 3 , 0.95g / cm 3 , 0.96g / cm 3 ,

[0023] 0.97g / cm 3 、0.98g / cm 3 , 0.99g / cm 3 etc.

[0024] In the above technical scheme, the melting point range of preferred LDPE is m1-m2, wherein m1 is 100-110°C (for example but not limited to m1 is 101°C, 102°C, 103°C, 104°C, 105°C, 106°C, 107°C, 108°C, 109°C, etc.), and m2 is 120-130°C (for example but not limited to m2 is 121°C, 122°C, 123°C, 124°C, 125°C, 126°C, 127°C, 128°C, 129°C, etc.).

[0025] The available LDPEs include the one produced by Beijing Yanshan Branch of China Petrochemical Corporation, with the grade LD605, the one produced by China Coal Energy Co., Ltd., with the grade DFDA-7042, and the one produced by Zhongtian Hechuang Energy Co., Ltd., with the grade PE M23D7 (LD-605).

[0026] For comparison purposes only, the examples and comparative examples of the present invention use the LD605 produced by Beijing Yanshan Branch of China Petrochemical Corporation, with a crystallinity of 56%, an MFR of 4 g / 10 min, and a density of 0.922 g / cm 3 , the melting point range is 108℃~125℃.

[0027] As non-limiting examples of the amount of micron silica aerogel, for example, but not limited to 0.2 parts, 0.4 parts, 0.6 parts, 0.8 parts, 1 parts, 1.2 parts, 1.4 parts, 1.6 parts, 1.8 parts, etc., more preferably 0.2-0.8 parts. Preferably, the D95 particle size of the silica aerogel is 10-100 microns, for example, but not limited to, the D95 particle size is 15 microns, 20 microns, 25 microns, 30 microns, 35 microns, 40 microns, 45 microns, 50 microns, 55 microns, 60 microns, 65 microns, 70 microns, 75 microns, 80 microns, 85 microns, 90 microns, 95 microns, etc. For comparison only, the micron silica aerogel used in the embodiment is produced by Suzhou Thermal Image Nanotechnology Co., Ltd., brand TEP-D50, and the D95 particle size is 50 microns.

[0028] In the above technical scheme, it is further preferred that the D95 particle size of nano silicon dioxide is 5 to 60nm (for example, but not limited to D95 is 25nm, 30nm, 35nm, 40nm, 45nm, 50nm, 55nm). According to the preparation process, nano silicon dioxide has precipitated nano silicon dioxide and gas phase nano silicon dioxide. Both precipitated nano silicon dioxide and gas phase nano silicon dioxide can be used in the present invention, and comparable technical effects have been achieved. According to whether the surface of silicon dioxide is hydrophobically treated, there is silicon dioxide without hydrophobic treatment, both of which can be used in the present invention, but the hydrophobic nano silicon dioxide has better compatibility with LDPE. As for the D95 particle size, we believe that the smaller the D95 particle size, the better, but the smaller the D95 particle size, the higher the economic cost. For comparison only, the nano-silica used in the present invention is nano-scale hydrophobic fumed silica with a grade of TSP-L20 supplied by Jiangsu Tianxing New Materials Co., Ltd. The fumed silica with a surface hydrophobic treatment has a D95 particle size of 15 nm.

[0029] In the present invention, the addition of micron silica aerogel improves the softness and compression rebound rate of pearl cotton; the addition of nano silica improves the quick-drying property and resilience of pearl cotton. In particular, when the micron silica aerogel is 0.2-0.8 parts, and the total amount of micron silica aerogel and nano silica is 1-3 parts (for example, but not limited to the total amount of micron silica aerogel and nano silica is 1.1 parts, 1.2 parts, 1.3 parts, 1.4 parts, 1.5 parts, 1.6 parts, 1.7 parts, 1.8 parts, 1.9 parts, 2 parts, 2.1 parts, 2.1 parts, 2.3 parts, 2.4 parts, 2.5 parts, 2.6 parts, 2.7 parts, 2.8 parts, 2.9 parts, etc.), pearl cotton has excellent quick-drying property, compression rebound resilience and softness, so that pearl cotton has the best comprehensive performance, is very suitable for filling materials for home textile and household products, and can also be directly used as cushions for various items.

[0030] In the above technical solution, the composition preferably includes 0.5 to 5 parts of talc, for example but not limited to 1 part, 1.5 parts, 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts, 4.5 parts, etc.

[0031] In the above technical scheme, the D95 particle size of talcum powder is preferably 1 to 20 microns, for example, but not limited to, the D95 particle size of talcum powder is 1.5 microns, 2 microns, 2.5 microns, 5 microns, 5.5 microns, 6 microns, 7 microns, 8 microns, 9 microns, 10 microns, 11 microns, 12 microns, 13 microns, 14 microns, 15 microns, 16 microns, 17 microns, 18 microns, 19 microns, etc., more preferably 1 to 10 microns. Only for year-on-year comparison, the talcum powder used in the embodiments and comparative examples is Chunxue brand talcum powder D95 with a particle size of 10 microns for foaming, produced by Qixia Huatai Talc Co., Ltd.

[0032] In the above technical solution, the composition preferably includes 0.5 to 5 parts of foam anti-shrinkage agent, for example but not limited to, the anti-shrinkage agent is 1 part, 1.5 parts, 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts, 4.5 parts, 5 parts, 5.5 parts, and the like.

[0033] There is no particular restriction on the type of anti-shrinkage agent, and those skilled in the art can reasonably choose it without creative work. For example, the anti-shrinkage agent can select a nonionic surfactant, preferably at least one of the material group consisting of monoglyceride, fatty alcohol polyoxyethylene ether, fatty acid polyoxyethylene ether ester and fatty acid monoethanolamide. The fatty acid described here can independently select fatty acids with carbon numbers of 10 to 18, such as but not limited to fatty acids with carbon numbers of 11, fatty acids with carbon numbers of 12, fatty acids with carbon numbers of 13, fatty acids with carbon numbers of 14, fatty acids with carbon numbers of 15, fatty acids with carbon numbers of 16, fatty acids with carbon numbers of 17, and the like. Fatty acid glycerides include monoglyceride, diglyceride and triglyceride. We experimentally found that only monoglyceride can contribute to the anti-shrinkage effect of the foaming process. Only for comparison, monostearate glyceryl is generally used as an anti-shrinkage agent in the embodiments of the present invention. The fatty alcohol referred to here can be a fatty alcohol with a carbon number of 10 to 18, such as but not limited to a fatty alcohol with a carbon number of 11, a fatty alcohol with a carbon number of 12, a fatty alcohol with a carbon number of 13, a fatty alcohol with a carbon number of 14, a fatty alcohol with a carbon number of 15, a fatty alcohol with a carbon number of 16, a fatty alcohol with a carbon number of 17, etc. For comparison only, the anti-shrinkage agent used in the embodiment of the present invention is a Jialishi brand plastic treasure SP-1 anti-shrinkage agent, the ingredient of which is glyceryl monostearate, produced by Jialishi Additive (Haian) Co., Ltd.

[0034] In the above technical solution, the composition preferably includes a foaming agent.

[0035] Those skilled in the art can make reasonable choices without creative work. The foaming agent can be an inorganic foaming agent or an organic foaming agent, and the inorganic foaming agent and the organic foaming agent can be physical foaming agents and chemical foaming agents respectively. The physical foaming agent only changes its volume from small to large during the foaming process, and the foaming agent itself does not undergo chemical changes during this process. During the foaming process of the chemical foaming agent, the foaming agent itself undergoes a decomposition reaction to produce gas.

[0036] As a non-limiting example, among inorganic foaming agents, nitrogen, argon, helium, carbon dioxide, air, and water are physical foaming agents, while sodium bicarbonate and the like are chemical foaming agents, and sodium bicarbonate decomposes to produce gas when heated;

[0037] As a non-limiting example, among organic foaming agents, hydrocarbon foaming agents (mainly C3-C5 hydrocarbons), halogenated hydrocarbon foaming agents (such as Freon), etc., are physical foaming agents; among organic foaming agents, foaming agents containing azo groups (such as azodicarbonamide) or foaming agents containing hydrazide structures (such as p-toluenesulfonylhydrazide, 3,3-disulfonylhydrazide diphenyl sulfone) use the property of generating nitrogen by thermal decomposition, and are chemical foaming agents.

[0038] For comparison only, butane is generally used as the foaming agent in the embodiments of the present invention.

[0039] As for the amount of foaming agent used, it is related to the type of foaming agent and the target product of the composition, and can be reasonably selected by those skilled in the art without the need for creative work.

[0040] As an example, the present invention uses butane as a foaming agent, and the amount is 10 to 45 parts, for example but not limited to 15 parts, 20 parts, 25 parts, 30 parts, 35 parts, 40 parts, etc., more preferably 15 to 40 parts. The butane used as a foaming agent can be normal butane and / or isobutane. For comparison only, the foaming agent used in the present invention is normal butane, which is produced by Qingdao Fengcheng Beiling Liquefied Gas Co., Ltd.

[0041] A second object of the present invention is to provide a material.

[0042] To achieve the second purpose, the technical solution is:

[0043] A novel quick-drying, soft and high-rebound material comprises a skeleton material and foams dispersed in the skeleton material, wherein the skeleton material is composed of any composition described in the technical solution of one of the above purposes. The composition herein does not include a foaming agent.

[0044] The third object of the present invention is to provide a method for preparing the above-mentioned material.

[0045] To achieve the third of the above objectives, the technical solution is:

[0046] The method for preparing the material in the technical solution of the second object comprises:

[0047] (1) uniformly mixing a required amount of LDPE masterbatch, a required amount of talcum powder, a required amount of nano-silicon dioxide, a required amount of silica aerogel and a required amount of anti-shrinkage agent to obtain material I;

[0048] (2) mixing material I with an anti-shrinkage agent to obtain material II;

[0049] (3) mixing material II with a foaming agent to obtain material III;

[0050] (4) extrusion molding of material III;

[0051] (5) Shape the pearl cotton product.

[0052] In the above-mentioned preparation method, the mixing temperature of step (1) is preferably 125°C or higher and lower than 220°C, for example but not limited to 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, 210°C, etc. More preferably, the mixing is first performed at a temperature T1 of 125°C to 150°C, and then at a temperature T2 of 180°C or higher and lower than 220°C.

[0053] In the above-mentioned preparation method, the mixing temperature T3 of step (2) is preferably 220-240°C, for example but not limited to T3 is 225°C, 230°C, 235°C, etc.;

[0054] In the above-mentioned preparation method, the mixing temperature T4 of step (3) is preferably above 190°C and below 220°C, for example but not limited to T4 is 195°C, 200°C, 205°C, 210°C, 215°C, etc.;

[0055] In the preparation method described above, the extrusion temperature in step (4) is preferably 80°C to 100°C, for example but not limited to 85°C, 90°C, 95°C, etc.

[0056] In the preparation method described above, the purpose of shaping is to prevent the extrudate in step (4) from sticking, so it is necessary to reduce the temperature of the extrudate to a temperature at which no more sticking occurs. Based on this principle, those skilled in the art can reasonably grasp the shaping temperature without having to make creative efforts. For example, in the preparation method of the present invention, the shaping temperature of the optional step (5) is below 50°C, for example but not limited to the shaping temperature of step (5) is -40°C, -35°C, -30°C, -25°C, -20°C, -15°C, -10°C, -5°C, 0°C, 5°C, 10°C, 15°C, 20°C, 25°C, 30°C, 35°C, etc.; further preferably -15°C to 45°C. Only for comparison, the shaping temperature in the present invention is 30°C.

[0057] In the above-mentioned preparation method, preferably, the single screw extruder comprises a barrel, a screw disposed in the barrel, and a die head at the end of the extruder.

[0058] In the preparation method described above, the aspect ratio of the screw is preferably 50-60, for example but not limited to, the aspect ratio of the screw is 51, 52, 53, 54, 55, 56, 57, 58, 59, etc.

[0059] In the preparation method described above, it is preferred that 10 temperature zones are set in the barrel, namely barrel zone 1, barrel zone 2, barrel zone 3, barrel zone 4, barrel zone 5, barrel zone 6, barrel zone 7, barrel zone 8, barrel zone 9 and barrel zone 10 from the beginning to the end of the barrel.

[0060] In the above-described preparation method, the temperatures of barrel zone 1, barrel zone 2, barrel zone 3, barrel zone 4, barrel zone 5, barrel zone 6, barrel zone 7, barrel zone 8, barrel zone 9, and barrel zone 10 are represented by T1, T2, T3, T4, T5, T6, T7, T8, T9, and T10, preferably T1 < T2 < T3 and preferably T3 > T4 > T5 > T6 > T7 > T8 > T9 ; Further preferably, 125℃≤T1≤150℃, 180℃≤T2<220℃, 220℃≤T3≤240℃, 190℃≤T4<220℃, 170℃≤T5<190℃, 150℃≤T6<170℃, 130℃≤T7<150℃, 110℃≤T8<130℃, 95℃≤T9<110℃, 80℃≤T10<95℃.

[0061] In the preparation method described above, a main feed port is preferably set in the barrel 1 area; the main feed port is used to add a premix of the main material (LDPE masterbatch) and auxiliary materials (the required amount of talcum powder, the required amount of nano-silicon dioxide, and the required amount of silica aerogel) except the anti-shrinkage agent and the foaming agent.

[0062] In the preparation method described above, it is preferred that an anti-shrinkage agent feed port is provided in the barrel 3 zone for injecting the anti-shrinkage agent.

[0063] In the preparation method described above, it is preferred to set a foaming agent feed port in the barrel 4 area for injecting the foaming agent.

[0064] In the above-mentioned preparation method, the temperature of the die head is preferably 80°C to 100°C, for example but not limited to the temperature of the die head is 85°C, 90°C, 95°C, etc.

[0065] In the preparation method described above, the shaping operation in the optional step (5) is carried out in a shaping drum.

[0066] The shape of the pearl cotton product is related to the die head used during extrusion. Those skilled in the art can reasonably select an extrusion die head with a suitable structure according to the final use of the pearl cotton product, without having to pay creative labor and can achieve comparable technical effects.

[0067] Only by comparison, the pearl cotton product obtained by the extrusion die head used in the embodiment of the present invention and the comparative example is in the shape of a diaphragm, and the thickness of the diaphragm is 4mm. According to the principle of the present invention, those skilled in the art can understand that when the die head used makes the pearl cotton product have other geometric shapes, the present invention can still achieve comparable technical effects.

[0068] In the embodiments and comparative examples of the present invention, the extruder used is a product of Longkou Jinmeng Machinery Co., Ltd., model: 135, screw diameter: 135MM, screw length: 7425MM.

[0069] For comparison purposes only, in the embodiments and comparative examples, the set temperatures of the various zones of the barrel, the die head and the shaping drum are shown in the following table:

[0070] Table 1

[0071]

[0072] In the embodiments and comparative examples, a main feed port is set in barrel 1 zone, and a premix of auxiliary materials (the required amount of talcum powder, the required amount of nano-silicon dioxide, the required amount of silica aerogel) and the main material (LDPE masterbatch) other than the anti-shrinkage agent and the foaming agent is added through this main feed port; an anti-shrinkage agent feed port is set in barrel 3 zone, and the anti-shrinkage agent is injected through this feed port; a foaming agent feed port is set in barrel 4 zone, and the foaming agent is injected through this feed port.

[0073] A fourth object of the present invention is to provide application of the novel quick-drying, soft and high-resilience material in home textile and household products.

[0074] For example, it can be used as a new filling material in home textiles and home furnishing products such as quilts, mattresses, seat cushions, pillows, neck pillows, carpets, quilted mats, Simmons mats, sofas, etc.; it can also be directly used as a mat for various items, such as coasters, storage box mats, and in addition to filling mattresses, carpets, quilted mats, Simmons mats, sofas, it can also be directly used as a pad under mattresses, carpets, quilted mats, Simmons mats, sofas, etc.

[0075] Performance evaluation of the novel quick-drying, soft and high-rebound material of the present invention

[0076] The newly prepared new quick-drying soft high-resilient material, the gas in the foam is the foaming agent, the foaming agent in the foam is naturally dissipated at room temperature after being placed for 4 to 7 days and is naturally replaced by air at the same time. The pearl cotton products in the specific embodiment of the present invention are all placed at room temperature for 10 days before the performance test is carried out.

[0077] 1) The quick-drying evaluation method is as follows:

[0078] 1000 g of the novel quick-drying, soft and highly resilient material obtained in the embodiments of the present invention and the comparative examples were put into a washing machine and washed according to the C4M method set in the Japanese fiber product home washing test method JIS L 1930-2014. After washing, the test product was taken out and hung in a constant temperature and humidity indoor environment with a wind speed of 5 m / min, a temperature of 25° and a relative humidity of 65%. The mass of the PE foam material was tested every 10 minutes. When the mass was less than or equal to 1100 g, the time used was recorded, and the quick-drying effect was evaluated according to Table 2:

[0079] Table 2

[0080]

[0081] 2) Evaluation of compression resilience

[0082] The novel quick-drying, soft, and highly resilient material obtained in the embodiments of the present invention and the comparative examples was cut into test pieces with a length and width of 20CM*20CM. Ten pieces of the test piece were stacked in a transparent container with a bottom of 20CM*20CM and a height of 20CM, and placed under the pressure arm of a single-arm fabric strength tester of model HD026. A pressure plate with a diameter of 20CM was used, and a gravity of 4.9 Newtons was used to press on it for 10 minutes, and the total height H0 of the 10 foamed materials was measured. The pressure was further increased to 196 Newtons, and the 10 foamed materials were pressed for 120 hours, and the total height H1 of the 10 foamed materials was measured. The pressure was removed, and the gravity of 4.9 Newtons was used to press on it for 10 minutes, and the total height H2 of the 10 foamed materials was measured. The compression rebound rate = (H2-H1) / (H0-H1)*100%, and the rating method is shown in Table 3 below.

[0083] Table 3

[0084] Rating 1 2 3 4 5 Compression rebound rate, % 91 and above 81-90 61-80 51-60 Below 50 Resilience evaluation Excellent rebound Good rebound Rebound Poor rebound No resilience

[0085] 3) Softness evaluation

[0086] The novel quick-drying, soft and highly resilient material obtained in the embodiments of the present invention and the comparative examples was cut into test pieces with a length and width of 20CM*20CM. Ten pieces of the test pieces were stacked into a transparent container with a bottom of 20CM*20CM and a height of 20CM. The container was placed under the pressure arm of a single-arm fabric strength tester model HD026. A pressure plate with a diameter of 20CM was used to press on the pressure plate with a gravity of 4.9N for 10 minutes. The total height H1 of the 10 pieces of foamed material was measured. The pressure of the pressure arm was increased and compressed to 60% of the height of H1. The maximum pressure value of the pressure arm was read and rated according to Table 4.

[0087] Table 4

[0088] Rating 1 2 3 4 5 Indentation hardness, N Below 65 66-125 126-185 186-309 310 or more Softness evaluation Super soft Softer soft Not soft Hard

[0089] The present invention is described in detail below by way of examples and comparative examples. DETAILED DESCRIPTION

[0090] [Example 1]

[0091] 1. Formulation

[0092] LDPE masterbatch, 100 parts;

[0093] Nano silicon dioxide, 1.0 part;

[0094] Talc, 3.0 parts;

[0095] Anti-shrinkage agent, 3.0 parts;

[0096] Foaming agent, 26 parts.

[0097] 2. Preparation of pearl cotton

[0098] At room temperature, mix the required amount of LDPE masterbatch, nano-silicon dioxide and talcum powder evenly to obtain a premix; confirm that the required temperature of each barrel area, die head and shaping drum has been set according to the parameters in Table 1, and start the equipment so that the equipment is in a feeding state. Add the aforementioned premix to the extruder through the main feed port set in barrel area 1, add the anti-shrinkage agent to the extruder through the anti-shrinkage agent feed port set in barrel area 3, and add the foaming agent to the extruder through the foaming agent feed port set in barrel area 4. Shape the extrudate from the extruder die head in the shaping drum to obtain pearl cotton. Take the pearl cotton product obtained after the equipment runs stably and place it at 26±2℃ for 10 days for performance testing.

[0099] 3. Pearl cotton performance test

[0100] After testing, the performance is as follows:

[0101] Quick drying: Drying time is 64 minutes, rating level 2;

[0102] Compression resilience: Compression resilience rate 73%, rating level 3;

[0103] Softness: Indentation hardness 426N, rated level 5.

[0104] [Example 2]

[0105] 1. Formulation

[0106] LDPE masterbatch, 100 parts;

[0107] Nano silicon dioxide, 2.0 parts;

[0108] Talc, 3.0 parts;

[0109] Anti-shrinkage agent, 3.0 parts;

[0110] Foaming agent, 26 parts.

[0111] 2. Preparation of pearl cotton

[0112] At room temperature, mix the required amount of LDPE masterbatch, nano-silicon dioxide and talcum powder evenly to obtain a premix; confirm that the required temperature of each barrel area, die head and shaping drum has been set according to the parameters in Table 1, and start the equipment so that the equipment is in a feeding state. Add the aforementioned premix to the extruder through the main feed port set in barrel area 1, add the anti-shrinkage agent to the extruder through the anti-shrinkage agent feed port set in barrel area 3, and add the foaming agent to the extruder through the foaming agent feed port set in barrel area 4. Shape the extrudate from the extruder die head in the shaping drum to obtain pearl cotton. Take the pearl cotton product obtained after the equipment runs stably and place it at 26±2℃ for 10 days for performance testing.

[0113] 3. Pearl cotton performance test

[0114] After testing, the performance is as follows:

[0115] Quick drying: Drying time is 47 minutes, rating level 1;

[0116] Compression resilience: Compression resilience rate 82%, rating level 2;

[0117] Softness: Indentation hardness 334N, rated level 5.

[0118] [Example 3]

[0119] 1. Formulation

[0120] LDPE masterbatch, 100 parts;

[0121] Micronized silica aerogel, 0.8 parts;

[0122] Nano silicon dioxide, 1.2 parts;

[0123] Talc, 3.0 parts;

[0124] Anti-shrinkage agent, 3.0 parts;

[0125] Foaming agent, 26 parts.

[0126] 2. Preparation of pearl cotton

[0127] At room temperature, mix the required amount of LDPE masterbatch, micron silica aerogel, nano silica and talcum powder to obtain a premix; confirm that the required temperature of each barrel area, die head and shaping drum has been set according to the parameters in Table 1, and start the equipment so that the equipment is in a feeding state. Add the aforementioned premix to the extruder through the main feed port set in barrel area 1, add the anti-shrinkage agent to the extruder through the anti-shrinkage agent feed port set in barrel area 3, and add the foaming agent to the extruder through the foaming agent feed port set in barrel area 4. Shape the extrudate from the extruder die head in the shaping drum to obtain pearl cotton. Take the pearl cotton product obtained after the equipment runs stably and place it at 26±2℃ for 10 days for performance testing.

[0128] 3. Pearl cotton performance test

[0129] After testing, the performance is as follows:

[0130] Quick drying: Drying time is 75 minutes, rating level 2;

[0131] Compression resilience: Compression resilience rate 86%, rating level 2;

[0132] Softness: Indentation hardness 52N, rated as level 1.

[0133] [Example 4]

[0134] 1. Formulation

[0135] LDPE masterbatch, 100 parts;

[0136] Micronized silica aerogel, 0.5 parts;

[0137] Nano silicon dioxide, 1.5 parts;

[0138] Talc, 3.0 parts;

[0139] Anti-shrinkage agent, 3.0 parts;

[0140] Foaming agent, 26 parts.

[0141] 2. Preparation of pearl cotton

[0142] At room temperature, mix the required amount of LDPE masterbatch, micron silica aerogel, nano silica and talcum powder to obtain a premix; confirm that the required temperature of each barrel area, die head and shaping drum has been set according to the parameters in Table 1, and start the equipment so that the equipment is in a feeding state. Add the aforementioned premix to the extruder through the main feed port set in barrel area 1, add the anti-shrinkage agent to the extruder through the anti-shrinkage agent feed port set in barrel area 3, and add the foaming agent to the extruder through the foaming agent feed port set in barrel area 4. Shape the extrudate from the extruder die head in the shaping drum to obtain pearl cotton. Take the pearl cotton product obtained after the equipment runs stably and place it at 26±2℃ for 10 days for performance testing.

[0143] 3. Pearl cotton performance test

[0144] After testing, the performance is as follows:

[0145] Quick drying: Drying time is 56 minutes, rating level 1;

[0146] Compression resilience: Compression resilience rate 93%, rating level 1;

[0147] Softness: Indentation hardness 63N, rated as level 1.

[0148] [Example 5]

[0149] 1. Formulation

[0150] LDPE masterbatch, 100 parts;

[0151] Micronized silica aerogel, 0.2 parts;

[0152] Nano silicon dioxide, 1.8 parts;

[0153] Talc, 3.0 parts;

[0154] Anti-shrinkage agent, 3.0 parts;

[0155] Foaming agent, 26 parts.

[0156] 2. Preparation of pearl cotton

[0157] At room temperature, mix the required amount of LDPE masterbatch, micron silica aerogel, nano silica and talcum powder to obtain a premix; confirm that the required temperature of each barrel area, die head and shaping drum has been set according to the parameters in Table 1, and start the equipment so that the equipment is in a feeding state. Add the aforementioned premix to the extruder through the main feed port set in barrel area 1, add the anti-shrinkage agent to the extruder through the anti-shrinkage agent feed port set in barrel area 3, and add the foaming agent to the extruder through the foaming agent feed port set in barrel area 4. Shape the extrudate from the extruder die head in the shaping drum to obtain pearl cotton. Take the pearl cotton product obtained after the equipment runs stably and place it at 26±2℃ for 10 days for performance testing.

[0158] 3. Pearl cotton performance test

[0159] After testing, the performance is as follows:

[0160] Quick drying: Drying time is 50 minutes, rating level 1;

[0161] Compression resilience: Compression resilience rate 81%, rating level 2;

[0162] Softness: Indentation hardness 124N, rated level 2.

[0163] [Example 6]

[0164] 1. Formulation

[0165] LDPE masterbatch, 100 parts;

[0166] Micronized silica aerogel, 0.5 parts;

[0167] Talc, 3.0 parts;

[0168] Anti-shrinkage agent, 3.0 parts;

[0169] Foaming agent, 26 parts.

[0170] 2. Preparation of pearl cotton

[0171] At room temperature, mix the required amount of LDPE masterbatch, micron silica aerogel and talcum powder to obtain a premix; confirm that the required temperature of each barrel area, die head and shaping drum has been set according to the parameters in Table 1, and start the equipment so that the equipment is in a feeding state. Add the aforementioned premix to the extruder through the main feed port set in barrel area 1, add the anti-shrinkage agent to the extruder through the anti-shrinkage agent feed port set in barrel area 3, and add the foaming agent to the extruder through the foaming agent feed port set in barrel area 4. Shape the extrudate from the extruder die head in the shaping drum to obtain pearl cotton. Take the pearl cotton product obtained after the equipment runs stably and place it at 26±2℃ for 10 days for performance testing.

[0172] 3. Pearl cotton performance test

[0173] After testing, the performance is as follows:

[0174] Quick drying: Drying time is 191 minutes, rating level 3;

[0175] Compression resilience: Compression resilience rate 76%, rating level 3;

[0176] Softness: Indentation hardness 105N, rated as level 2.

[0177] [Example 7]

[0178] 1. Formulation

[0179] LDPE masterbatch, 100 parts;

[0180] Micronized silica aerogel, 1.0 part;

[0181] Talc, 3.0 parts;

[0182] Anti-shrinkage agent, 3.0 parts;

[0183] Foaming agent, 26 parts.

[0184] 2. Preparation of pearl cotton

[0185] At room temperature, mix the required amount of LDPE masterbatch, micron silica aerogel and talcum powder to obtain a premix; confirm that the required temperature of each barrel area, die head and shaping drum has been set according to the parameters in Table 1, and start the equipment so that the equipment is in a feeding state. Add the aforementioned premix to the extruder through the main feed port set in barrel area 1, add the anti-shrinkage agent to the extruder through the anti-shrinkage agent feed port set in barrel area 3, and add the foaming agent to the extruder through the foaming agent feed port set in barrel area 4. Shape the extrudate from the extruder die head in the shaping drum to obtain pearl cotton. Take the pearl cotton product obtained after the equipment runs stably and place it at 26±2℃ for 10 days for performance testing.

[0186] 3. Pearl cotton performance test

[0187] After testing, the performance is as follows:

[0188] Quick drying: Drying time is 216 minutes, rating level 3;

[0189] Compression resilience: Compression resilience rate 88%, rating level 2;

[0190] Softness: Indentation hardness 59N, rated as level 1.

[0191] [Comparative Example 1]

[0192] 1. Formulation

[0193] LDPE masterbatch, 100 parts;

[0194] Talc, 3.0 parts;

[0195] Anti-shrinkage agent, 3.0 parts;

[0196] Foaming agent, 26 parts.

[0197] 2. Preparation of pearl cotton

[0198] At room temperature, mix the required amount of LDPE masterbatch and talcum powder evenly to obtain a premix; confirm that the required temperature of each barrel area, die head and shaping drum has been set according to the parameters in Table 1, and start the equipment so that the equipment is in a feeding state. Add the aforementioned premix to the extruder through the main feed port set in barrel area 1, add the anti-shrinkage agent to the extruder through the anti-shrinkage agent feed port set in barrel area 3, and add the foaming agent to the extruder through the foaming agent feed port set in barrel area 4. Shape the extrudate from the extruder die head in the shaping drum to obtain pearl cotton. Take the pearl cotton product obtained after the equipment runs stably and place it at 26±2℃ for 10 days for performance testing.

[0199] 3. Pearl cotton performance test

[0200] After testing, the performance is as follows:

[0201] Quick drying: Drying time is 94 minutes, rating level 2;

[0202] Compression resilience: Compression resilience rate 36%, rating 5;

[0203] Softness: Indentation hardness 362N, rated level 5.

[0204] [Comparative Example 2]

[0205] 1. Formulation

[0206] Except that micronized silica gel is replaced by micronized silica of equal weight, the other components in the formula are the same as those in Example 7. The specific formula is:

[0207] LDPE masterbatch, 100 parts;

[0208] Micronized silicon dioxide, 1.0 part;

[0209] Talc, 3.0 parts;

[0210] Anti-shrinkage agent, 3.0 parts;

[0211] Foaming agent, 26 parts.

[0212] The micron silicon dioxide is produced by Guangzhou Xiyi Chemical Co., Ltd., with brand CE923 and D95 ​​of 55 microns.

[0213] 2. Preparation of pearl cotton

[0214] At room temperature, mix the required amount of LDPE masterbatch, micron silicon dioxide and talcum powder to obtain a premix; confirm that the required temperature of each barrel area, die head and shaping drum has been set according to the parameters in Table 1, and start the equipment so that the equipment is in a feeding state. Add the aforementioned premix to the extruder through the main feed port set in barrel area 1, add the anti-shrinkage agent to the extruder through the anti-shrinkage agent feed port set in barrel area 3, and add the foaming agent to the extruder through the foaming agent feed port set in barrel area 4. Shape the extrudate from the extruder die head in the shaping drum to obtain pearl cotton. Take the pearl cotton product obtained after the equipment runs stably and place it at 26±2℃ for 10 days for performance testing.

[0215] 3. Pearl cotton performance test

[0216] After testing, the performance is as follows:

[0217] Quick drying: Drying time is 86 minutes, rating level 2;

[0218] Compression resilience: Compression resilience rate 65%, rating level 3;

[0219] Softness: Indentation hardness 531N, rated level 5.

Claims

1. A composition for producing pearl cotton, comprising, by weight: High pressure low density polyethylene, 100 parts; Micronized silica aerogel, greater than 0 and 2 parts; Nano-silicon dioxide, greater than 0 and 2 parts. Preferably, the D95 particle size of the silica aerogel is 10 to 100 microns; and / or preferably, the LDPE crystallinity is 55% to 60%; and / or preferably, the MFR (i.e., melt flow rate) of the LDPE is 1.5 to 4.5 g / 10 min; and / or preferably, the density of the LDPE is 0.9 to 1.0 g / cm 3 ; and / or preferably the melting point range of LDPE is m1-m2, wherein m1 is 100-110°C and m2 is 120-130°C; high pressure low density polyethylene, referred to as LDPE.

2. The composition according to claim 1, characterized in that: The particle size of nano-silicon dioxide D95 is 5 to 60 nm.

3. The composition according to claim 1, characterized in that The composition comprises 0.5 to 5 parts of talc powder, and preferably the D95 particle size of the talc powder is 1 to 20 microns. And / or, the composition comprises 0.5 to 5 parts of foam anti-shrinkage agent.

4. The composition according to claim 3, characterized in that The anti-shrinkage agent is a nonionic surfactant, preferably at least one selected from the group consisting of monoglyceride of fatty acid, polyoxyethylene fatty alcohol ether, polyoxyethylene fatty acid ether ester and monoethanolamide of fatty acid.

5. The composition according to claim 1, characterized in that: The composition includes a blowing agent.

6. A novel quick-drying, soft and high-rebound material, comprising a skeleton material and foams dispersed in the skeleton material, wherein the skeleton material is composed of the composition described in any one of claims 1 to 4.

7. The method for preparing the novel quick-drying, soft and high-rebound material according to claim 6, comprising: (1) uniformly mixing a required amount of LDPE masterbatch, a required amount of talcum powder, a required amount of nano-silicon dioxide, a required amount of silica aerogel and a required amount of anti-shrinkage agent to obtain material I; (2) mixing material I with an anti-shrinkage agent to obtain material II; (3) mixing material II with a foaming agent to obtain material III; (4) extrusion molding of material III; (5) Shape the pearl cotton product.

8. The preparation method according to claim 7, characterized in that The mixing temperature of step (1) is 125°C or higher and lower than 220°C; more preferably, the mixture is first mixed at a temperature T1 of 125°C to 150°C, and then mixed at a temperature T2 of 180°C or higher and lower than 220°C; And / or preferably the mixing temperature T3 of step (2) is 220-240°C; and / or preferably the mixing temperature T4 of step (3) is above 190° C. and below 220° C.; and or preferably the extrusion temperature in step (4) is 80°C to 100°C, And / or the temperature of the shaping in step (5) is preferably below 50°C.

9. The preparation method according to claim 8, characterized in that The preparation method is carried out in a device including a single screw extruder. The single screw extruder includes a barrel, a screw placed in the barrel, and a die head at the end of the extruder; The preferred aspect ratio of the screw is 50 to 60; Preferably, 10 temperature zones are set in the machine barrel, which are machine barrel zone 1, machine barrel zone 2, machine barrel zone 3, machine barrel zone 4, machine barrel zone 5, machine barrel zone 6, machine barrel zone 7, machine barrel zone 8, machine barrel zone 9, and machine barrel zone 10 from the beginning to the end of the machine barrel; The temperatures of barrel zone 1, barrel zone 2, barrel zone 3, barrel zone 4, barrel zone 5, barrel zone 6, barrel zone 7, barrel zone 8, barrel zone 9, and barrel zone 10 are represented by T1, T2, T3, T4, T5, T6, T7, T8, T9, and T10, preferably T1<T2<T3 and preferably T3>T4>T5>T6>T7>T8>T9; further preferably Select 125℃≤T1≤150℃, 180℃≤T2<220℃, 220℃≤T3≤240℃, 190℃≤T4<220℃, 170℃≤T5<190℃, 150℃≤T6<170℃, 130℃≤T7<150℃, 110℃≤T8<130℃, 95℃≤T9<110℃, 80℃≤T10<95℃; Preferably, the main feed port is arranged in the barrel 1 area; Preferably, an anti-shrinkage agent feed port is provided in the barrel 3 zone; Preferably, a foaming agent feed port is provided in the barrel 4 area; The temperature of the die head is preferably 80°C to 100°C.

10. Application of the novel quick-drying, soft, and highly resilient material described in claim 6 in home textile and home furnishing products. For example, it can be used as a novel filling material in home textile and home furnishing products such as quilts, mattresses, seat cushions, pillows, neck pillows, carpets, quilted pads, Simmons pads, sofas, etc.; it can also be directly used as a cushion for various items, such as coasters, storage box cushions, and in addition to being filled in mattresses, carpets, quilted pads, Simmons pads, and sofas, it can also be directly used as a cushion under mattresses, carpets, quilted pads, Simmons pads, and sofas, etc.